(3YbhO GdJfbjH Yf GdfaW hEfJGLg (B:s (3OQGSI bGfhfjI JMdjdjI ebGQfI (B/s - (3EHQGgje, cGhGf ESeGYjds ((3GdEScfOQjI (B[(3eUQ(B] :s (3GdecJH GdLGeYj GdMOjK,s, 2017)
(3hJgOa OQGSI ehVhY YbhO GdJfbjH Yf GdfaW hEfJGLg Edi JhVjM hHjGf eG jdj (B: (3ef gh UGMH edcjI GdKQhI GdfaWjI aj GdOSGJjQ hGdJTQjYGJ GdefXeI ddKQhI GdfaWjI aj GdOhd GdefJLI ddfaW ? hcPdc HjGf ehba GdTQjYI GdESdGejI Mhd edcjI GdeYGOf hef VefgG GdKQhI GdfaWjI, hcPdc HjGf eOi UdGMjGJ GdCbGdje Ch GdhdGjGJ GdechfI ddOhdI GdajOQGdjI aj GdJUQa HGdKQhI GdfaWjI ef NdGd YQV JMdjdj dehba OSGJjQ GdOhd GdGJMGOjI eY GdJQcjR Ydi UdGMjI Ebdje chQOSJGf GdYQGb aj GdJUQa HGdKQhI GdfaWjI GdcGefI aj CQGVj GdEbdje hHjGf eOi EecGfjI gPg GdCbGdje aj GdJYGbO eY GdTQcGJ GdCLfHjI dZQV GdJfbjH Yf GdfaW hEfJGLg(B. (3eHOC GdSjGOI GdOGFeI Ydi GdKQhGJ GdWHjYjI ef NdGd YQV JCQjNj dgPG GdeHOC aj CQhbI efXeI GdCee GdeJMOI hHjGf Cge GdbQGQGJ GdUGOQI(B.s
(3JUeje GdZdGa (B: (3QMGH(B.s
(3HHdjhLQGajI (B: (3UaMI (B385-410.s
Keywords: (3GdHJQhds -- (3bhGfjf hJTQjYGJs; (3GdHJQhds -- (3JfbjHs -- (3bhGfjf hJTQjYGJs; (3GdHJQhd (B((3bGfhf Ohdj(B)s